AJARAN TATTWA DALAM KAKAWIN PŪJA SARAŚWATI - I Wayan Arya Adnyana (Jurnal Pendidikan Agama, 2022)
The purpose of this study is to improve understanding of knowing the teachings of Tatwa in the kakawin Pūja Saraśwati. This data is obtained using the right method so that the data obtained can support the results of the research. This type of research is qualitative research because it is a text or literature study whose primary data source is kakawin Pūja Saraśwati. Literature studies is used as a method of data collection and then descriptive qualitative data processing is carried out. This study uses concepts to describe the issues to be discussed. The results of Pūja Saraśwati's research contain tattwa teachings, which emphasize many noble values in performing worship. The main cult is when there is harmony between actions and sincere thoughts. Birthly worship to Sang Hyang Aji Saraśwati can be done by presenting flowers that are a symbol of God and a symbol of sincerity of heart. Flowers that should be offered are flowers that are not rotten in the sense of not eaten by caterpillars, past the blooming period and dirty flowers in the sense of not containing ants and growing in graves.